Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376218
|View full text |Cite
|
Sign up to set email alerts
|

ArguLens: Anatomy of Community Opinions On Usability Issues Using Argumentation Models

Abstract: facilitated the review of lengthy issues. ArguLens provides the direction of designing valuable tools for high-level reasoning and effective discussion about usability.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 51 publications
(55 reference statements)
0
30
0
Order By: Relevance
“…These studies further demonstrated the complexity of issue discussions in the OSS context. Recognizing this complexity, Wang et al [5] proposed the use of an argumentation model, as well as the corresponding automated technique, to help extract and consolidate the diverse topics and opinions that the OSS community members post in ITSs. Our work is built upon these previous studies to further investigate the roles of emotions in the already complex OSS issue discussions.…”
Section: A Oss Issue Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies further demonstrated the complexity of issue discussions in the OSS context. Recognizing this complexity, Wang et al [5] proposed the use of an argumentation model, as well as the corresponding automated technique, to help extract and consolidate the diverse topics and opinions that the OSS community members post in ITSs. Our work is built upon these previous studies to further investigate the roles of emotions in the already complex OSS issue discussions.…”
Section: A Oss Issue Discussionmentioning
confidence: 99%
“…On the one hand, OSS communities' heterogeneous nature provides diverse perspectives that help a healthy advancement of the project. On the other hand, consolidating the varied perspectives in a large amount of community-generated requests and discussions is a challenging issue [5]. This challenge is particularly exacerbated by the complex emotions and affective states from the community participants manifested in the issues [6].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many OSS usability practices and discussions take place in an ad-hoc manner and, especially on OSS platforms such as GitHub (www.github.com), within a repository's issue tracking system [2,13,15]. Cheng and Guo [2] found usability specific issue threads on GitHub to be lengthy and contain over-generalized assumptions.…”
Section: D5mentioning
confidence: 99%
“…Due to its affinity for supporting various asynchronous activities, GitHub has enabled a vibrant community for remote collaboration and development of OSS projects. While there are many tools that can potentially be used for monitoring usability interests on GitHub OSS's, such as Issue tracking, there is currently no mature method for end user community collaboration [13,15,16]. Consequently, if any design decisions are made through input from end users, there are difficulties with properly communicating these decisions to other team members due to a lack of design artifacts clearly documenting the process.…”
mentioning
confidence: 99%
“…There are also works that tackled all the levels mentioned by Wambsganss et al (2020) . In Wang et al (2020 ), the authors deal with online discussions about usability on issue-tracking systems of open-source projects. Since a large number of issues and comments with different perspectives are posted daily, the contributors of projects face a major challenge in digesting the rich information embedded in the issue-tracking systems to determine the actual user needs and consolidate the diverse feedback.…”
Section: Background Knowledge and Related Workmentioning
confidence: 99%